Aechmea aenigmatica (Bromeliaceae; Bromelioideae) a new species from the state of Oaxaca, Mexico - López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo; Ceja-Romero, Jacqueline; Mendoza-Ruiz, Aniceto (Instituto de Ecología, A.C., 2011)
Aechmea aenigmatica López-Ferrari, Espejo, Ceja et A. Mendoza, a new species from Oaxaca, Mexico is described and illustrated. The new taxon is compared with A. lueddemanniana (K. Koch) Mez and A. mexicana Baker, species with similar characteristics, from which it differs by the presence of symmetrical sepals and petals without basal appendages. Identification keys for all species of Aechmea present in Oaxaca, as well as for all species of subgenus Podaechmea are included.